(untitled) (Journal of Patan Academy of Health Sciences, 2021)
Obstructed labour is a common cause of vesicovaginal fistula in the developing world. Those fistulae occurring after labour and its complications is called obstetric fistula. We report a case of complex obstetric fistula in a 32 y woman who was having continuous leakage of urine since last 10 y following caesarean section for obstructed labour. A successful fistula repair was done with transvaginal approach with Latzko technique and interposition with Martius flap.